DNA barcoding of Podonomus (Chironomidae, Podonominae) enables stage association of a named species and reveals hidden diversity in Brazilian inselbergs - Trivinho-Strixino, Susana; Pepinelli, Mateus; Siqueira, Tadeu [UNESP]; Roque, Fabio de Oliveira (Edp Sciences S A, 2012)
Podonomus Philippi was recently found in Brazilian inselbergs. In this study, we used sequences from the barcode region of cytochrome c oxidase I (COI) to assess Podonomus molecular diversity from mountains in Southeastern Brazil. Our results revealed the adult female and the larvae of Podonomus pepinellii Roque and Trivinho-Strixino, 2004 and extended the known geographical distribution of the species. Moreover, we found high molecular divergence in two populations located in the Serra da Mantiqueira and Serra do Espinhaco mountain range when compared with the only species recorded to Brazil, indicating the possibility of two more species to be described.
Keywords: Diptera; molecular identification; immature stages; cytochrome c oxidase I